ACM/IEEE SC 2005 Conference (SC'05)
DOI: 10.1109/sc.2005.47
|View full text |Cite
|
Sign up to set email alerts
|

Network Traffic Analysis With Query Driven Visualization SC 2005 HPC Analytics Results

Abstract: Our analytics challenge is is to identify, characterize, and visualize anomalous subsets of large collections of network connection data. We use a combination of HPC resources, advanced algorithms, and visualization techniques. To effectively and efficiently identify the salient portions of the data, we rely on a multi-stage workflow that includes data acquisition, summarization (feature extraction), novelty detection, and classification. Once these subsets of interest have been identified and automatically ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are a number of ways to parallelize TelegraphCQ to handle the stream volume [22], or alternatively the system can use Data Triage [19] to trade off result accuracy for speed. In terms of handling historical data, FastBit has been shown to parallelize well [25]. Overall, we anticipate the system we propose can be parallelized effectively on a modest cluster of computers.…”
Section: Related Workmentioning
confidence: 94%
See 2 more Smart Citations
“…There are a number of ways to parallelize TelegraphCQ to handle the stream volume [22], or alternatively the system can use Data Triage [19] to trade off result accuracy for speed. In terms of handling historical data, FastBit has been shown to parallelize well [25]. Overall, we anticipate the system we propose can be parallelized effectively on a modest cluster of computers.…”
Section: Related Workmentioning
confidence: 94%
“…In an number of performance measurements, WAH compressed indices were shown to significantly outperform other indices [27,28]. Re-cently, FastBit has also been used in analysis of network traffic data and shown to be able to handle massive data sets [25,2]. This makes it a convenient choice for our prototype.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel coordinates plots (PCPs) [11] are a well-researched visualization technique for multi-dimensional data. Studies have shown that they can be learned easily by non-visualization experts [15,16] and used in practice in various domains like finance [1], traffic safety [7], and network analysis [17]. Compared to related techniques such as scatter plot matrices and projections, PCPs have the advantage to identify, explore, and understand patterns across multiple dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has identified compressed bitmap indexes as a very effective indexing technology for network traffic data [5,12,13]. Bitmap indexes are more compact in size than competitive approaches, such as tree-based indexes, and provide significant speedup over complex multiattribute queries.…”
Section: Introductionmentioning
confidence: 99%